Clinicopathological Analysis of Ameloblastoma in a Northwestern Libyan Population: A 21-Year Retrospective Study - Shanab, Asmaa; Ben Sofia, Dunya (Khalij-Libya Journal of Dental and Medical Research, 2023)
Objectives. The purpose of this study was to evaluate the prevalence and clinicopathological characteristics of ameloblastoma in a Northwestern Libyan population. Methods. A 21-year retrospective study of ameloblastoma cases histopathologically diagnosed at Tripoli University Hospital, Tripoli, Libya, archived from 2002 to 2022. Basic clinicopathological data, including age at diagnosis, gender, anatomical tumor location, and histopathological diagnosis, were collected and analyzed retrospectively. The diagnosis was based on the criteria of the latest updating fifth edition of the 2022 WHO classification of Head and Neck Tumors. The collected data were analyzed by IBM SPSS Statistics for Windows version 26.0. Results. Ameloblastoma tumors constituted 2.3% of all 2308 registered orofacial biopsy specimens. A total of 44 cases of ameloblastoma tumors were analyzed. Of these, 30 (68.2%), 12 (27.3%), and 2 (4.5%) cases were of conventional, unicystic, and peripheral types, respectively. Regarding gender, 54.5% of cases occurred in males; the male-to-female ratio was 1.2:1. The most frequent anatomical location was the mandible (81.8%), with a mandible-to-maxilla ratio of 6:1. The majority of cases were diagnosed as a painless swelling (80%). A wide age range (15 to 78 years) was recorded, with the mean age of all patients at diagnosis was 36.6 ± 16.2 years. The peak incidence was in the fifth and third decades of life. Follicular ameloblastoma was the most common histopathological subtype (29.3%), followed by plexiform ameloblastoma (25.0%). No statistically significant associations were found between types/subtypes of ameloblastoma tumors with regard to gender and age group distribution (p > 0.05). Conclusion. The profile of the ameloblastoma tumors included in this Northwestern Libyan sample was similar to the profile described for most other worldwide populations. The collected data in this study provides baseline data on types of ameloblastoma tumors, which is of significance to the oral pathologist and maxillofacial surgeon.